Estimation of extreme temperatures in direct solar methane pyrolysis within a porous medium - Xu, Hengrui; Abuseada, Mostafa; Ju, Y. Sungtaek; Spearrin, R. Mitchell; Fisher, Timothy S. (Frontiers in Nanotechnology, 2025)
Porous media have wide application in renewable energy conversion processes, such as solar-thermal fuels production and decarbonization. Heat transport mechanisms within porous media can be highly complex, particularly under extreme conditions encountered in concentrated solar thermal reactors in which direct measurement of temperature is challenging. Here, we implement and report an inverse heat conduction model to estimate the temperature distribution throughout a porous substrate domain in a direct solar methane pyrolysis process. By solving a two-dimensional heat transfer problem and applying an inverse optimization algorithm, we estimate the quasi-steady state spatial temperature distribution in a fibrous porous carbon substrate. The results are validated indirectly by experimentally measured graphite deposition and a simplified reaction kinetic model.